Tuberculosis prevention and control dilemmas and strategic considerations along the China-Russia border under the visa-free policy - Nan WANG; Yanfu WANG; Zhaoyue LIU; Lin WU; Xinru LIU; Yajie FENG; Huanyu ZHANG; Junping LIU; Yue ZHOU; Xinle YIN; Yaping LIU; Libo LIANG (Editorial Office of Chinese Journal of Public Health, 2024)
In the post-pandemic era, the resumption of visa-free group travel services between China and Russia has led to frequent population movements, posing a substantial risk of infectious disease transmission in the border regions of the two countries. Tuberculosis (TB) is currently the second leading cause of death from infectious diseases worldwide, and both China and Russia are high-TB-burden countries. This creates specific challenges for TB prevention and control in the border areas. There is an urgent need to deeply explore weaknesses in the TB epidemic prevention and control efforts along the China-Russia border. Strategies such as the development of intelligent border ports, enhancement of international exchange and cooperation, improvement of the public health collaborative governance capacity of both countries, optimization of health resource allocation in port areas, and strengthening the awareness of customs quarantine personnel and border residents regarding TB prevention and control, must be constructed. These strategies aim to comprehensively promote the joint construction of a human health and wellness community by China and neighboring countries.